Transgressions, Conflicts and Reconciliations In The God of Small Things: - (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The title of the novel, “THE GOD OF SMALL THINGS” strikesa great deal of artistic significance as it is a vivid depiction of how thesmall things in life affect people’s behavior and their lives. In turn thenovel shows how certain incidents in life lead to a series of conflictsnecessitating a gamut of reconciliations.